Comparison of Affected-Vertebra Fixation of Cortical Bone Trajectory Screw and Pedicle Screw for Lumbar Tuberculosis: A Minimum 3-Year Follow-Up. (21st July 2022) - Zhang, Peng; Ye, Jiekai; Huang, Lixia; Ying, Xiaozhang; Zhu, Bo; Jin, Yanghui; Fei, Jun; Shi, Shiyuan; Zheng, Qi
Abstract : Purpose . This study is aimed at comparing the clinical efficacy of cortical bone trajectory (CBT) screw fixation and pedicle screw (PS) fixation of the affected vertebrae in lumbar tuberculosis. Methods . We retrospectively analyzed the outcomes in 52 patients (27 cases in the CBT group, 25 cases in the PS group) with lumbar TB who underwent posterior affected-vertebra fixation combined with anterior debridement and bone grafting. The intraoperative blood loss, operative time, visual analog scale (VAS) scores for incision pain and leg pain, Japanese Orthopedic Association (JOA) score, bone grafting fusion, and complications were recorded. Results . All patients were followed up for 35-52 months and achieved good clinical outcomes. There were no differences between the two groups in the operative time, intraoperative blood loss, JOA score, bone grafting fusion, and complications. However, there was a significant difference between the two groups in VAS scores for incision pain on the 1st day and 3rd day after surgery. At the last follow-up, JOA scores were significantly improved in both groups compared to the preoperation. Conclusion . This retrospective study confirmed that both the affected-vertebra CBT screw fixation and PS fixation for lumbar TB via posterior and anterior approaches could achieve satisfactory outcomes, while the former resulted in better improvement for postoperative VAS scores.